Do web-quest technologies enhance socio-cultural competence in a language learning environment? - Sarzhanova, Dinara; Shokparov, Alibek; Akeshova, Madina; Rizakhojayeva, Gulnara (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the didactic potential of digital technologies in fostering socio-cultural competence among students at language universities. The research focuses on the development and application of web-quest projects as an interactive learning tool that enhances linguistic and multicultural education through digital means. The increasing demand for foreign language proficiency, including socio-cultural competence, and the lack of effective computer-based teaching methods justify the relevance of this study. The study employed a mixed-methods research design, incorporating a systematic literature review, observational analysis, and survey-based data collection. Additionally, experimental testing of developed web-quest projects was conducted to assess their effectiveness in improving students' socio-cultural competence. The research investigated how digital and telecommunication technologies contribute to computer-mediated intercultural communication, beyond merely serving as a medium for acquiring new knowledge. The results confirmed that web-quest technologies significantly enhance students’ socio-cultural competence by deepening their understanding of cultural realities, traditions, habits, and behavioral patterns of native speakers of the target language. The study also demonstrated that web-quests promote interactive cognitive creativity, enabling students to integrate and process information more effectively. As a result, a digital socio-cultural learning support framework was developed, leveraging modern computer technologies for foreign language education. The integration of web-quests in foreign language education fosters active engagement, knowledge integration, and cognitive creativity. The study highlights the importance of structured digital resources in improving socio-cultural awareness and facilitating immersive language learning experiences. This research provides language educators with a practical digital methodology for implementing web-quest-based learning. The findings suggest that incorporating digital tools into language curricula can enhance students’ socio-cultural competence and better prepare them for real-world intercultural interactions. Further research is encouraged to explore the long-term impact of web-quest technologies and their scalability in diverse language-learning environments.